PENERAPAN STRATEGI KWL (KNOW-WANT TO KNOW-LEARNED) PADA KETERAMPILAN MEMBACA PEMAHAMAN PESERTA DIDIK KELAS III SD - Widya Noviyanti; Nanang Khoirul Umam; Arissona Dia Indah Sari (JUSEDA, 2022)
Reading is one aspect of language skills. Reading comprehension skills are the ability of students after reading to obtain information and understand the meaning contained in the reading text. However, some students are able to read but do not understand the content of what has been read. The application of the KWL (Know-Want to Know-Learned) strategy can make students active during the process before, during, and after reading, so it is suitable to be applied to reading comprehension lessons. This research is a qualitative descriptive study that aims to describe the process, results and difficulties experienced by students in implementing the KWL (Know-Want to Know-Learned) strategy during the learning process. In this study using data collection techniques in the form of tests, interviews, observation and documentation. While the data analysis in this study is in the form of data reduction, data presentation, and drawing conclusions. The results of this study indicate that the activities of students at the second meeting were able to follow the KWL steps than at the first meeting. The ability of students when working on questions at the second meeting was more independent and increased than the first meeting. The difficulty faced by students is when making conclusions from the contents of the reading text